THE USE OF WELL WATER AND THE IMPACT OF MICROBIAL CONTAMINATION ON PUBLIC HEALTH - Luka, Ornela; Puto, Klementina; Kalluçi, Eglantina (LPPM Universitas Jambi, 2025)
In the region of Shkodra, private wells serve as a source of water for some families, both in urban and rural areas, for many activities. The main purpose of this study was to comprehensively assess the microbial quality of well water, with the aim of understanding its potential impact on public health among populations who use this water for daily consumption. The study included 10 monitoring stations during the period September 2023 to August 2024 with a total of 80 water samples were analysed, for Intestinal enterococci and Escherichia coli. The application method for microbiological use of well water is that of the ISO membrane filter ISO7899-2:2000, SM 922 B-2015. Intestinal enterococci dominated in 65% of the samples. As for the water source diseases encountered by residents, E. coli infections dominate with 90.36%, S. typhimurium 8.36%. From the correlation analysis result Escherichia coli disease correlates 80% with the presence of Intestinal enterococci in well water and 80% presence of Escherichia coli disease. The results of this study demonstrate that the high presence of pathogens in well water poses a risk to public health. Well contamination is mainly caused by untreated wastewater, nearby septic tank, animal waste. The novelty of this study lies in the fact that, for the first time, a correlation was applied between the microbial contamination of well water and the diseases resulting from its use, thereby confirming the relationship between water quality and public health.